The Role of Manganese Superoxide Dismutase in Inflammation Defense - Li, Chang (SAGE-Hindawi Access to Research, 2011)
Antioxidant enzymes maintain cellular redox homeostasis. Manganese superoxide dismutase (MnSOD), an enzyme located in mitochondria, is the key enzyme that protects the energy-generating mitochondria from oxidative damage. Levels of MnSOD are reduced in many diseases, including cancer, neurodegenerative diseases, and psoriasis. Overexpression of MnSOD in tumor cells can significantly attenuate the malignant phenotype. Past studies have reported that this enzyme has the potential to be used as an anti-inflammatory agent because of its superoxide anion scavenging ability. Superoxide anions have a proinflammatory role in many diseases. Treatment of a rat model of lung pleurisy with the MnSOD mimetic MnTBAP suppressed the inflammatory response in a dose-dependent manner. In this paper, the mechanisms underlying the suppressive effects of MnSOD in inflammatory diseases are studied, and the potential applications of this enzyme and its mimetics as anti-inflammatory agents are discussed.